Wound Healing Activity of Ficus racemosa Linn Fruit Extract - Rao, Krishnamoorthy M (International Journal of Pharmaceutical & Biological Archive, 2011)
ABSTRACT The wound healing activity of topically applied extract of fruit of Ficus racemosa Linn was evaluated in albino rat by excision wound model for a period of 16 days. Extract of Ficus racemosa Linn showed marked reduction in wound area in comparison to control group from 4th day onwards. The result obtained indicates that aqueous extract of Ficus racemosa Linn accelerates the wound healing process by decreasing the surface area of the wound.